Urinary nerve growth factor level could be a potential biomarker for diagnosis of overactive bladder - Liu, Hsin-Tzu; Kuo, Hann-Chorng (The Journal of urology, 2008)
The clinical diagnosis of overactive bladder has great variation and is based on subjective symptoms. This study was designed to measure urinary nerve growth factor levels in patients with different types of overactive bladder and to evaluate whether urinary nerve growth factor could be a biomarker for the diagnosis of overactive bladder. Urinary nerve growth factor levels were measured in patients with increased bladder sensation, overactive bladder dry and overactive bladder wet, and in a group of control subjects without lower urinary tract symptoms. Measurement of urinary nerve growth factor levels was performed by the enzyme-linked immunosorbent assay. The total urinary nerve growth factor levels were then normalized to the concentration of urinary creatinine (nerve growth factor/creatinine level). Comparison was performed using the nerve growth factor/creatinine level in all subgroups. Urinary nerve growth factor/creatinine levels were low in normal controls (0.041 +/- 0.026) and patients with increased bladder sensation (0.033 +/- 0.02). Patients with overactive bladder dry (0.39 +/- 0.08) or overactive bladder wet (1.7 +/- 0.26) had significantly higher urinary nerve growth factor levels compared to the controls and patients with increased bladder sensation. Patients with overactive bladder wet had significantly higher urinary nerve growth factor levels than those with overactive bladder dry (p = 0.000). The sensitivity of a urinary nerve growth factor/creatinine level of more than 0.05 in the diagnosis of overactive bladder dry or overactive bladder wet was 67.9% and the specificity was 93.8%. Patients with overactive bladder dry or overactive bladder wet had significantly higher urinary nerve growth factor levels compared to the control group and patients with increased bladder sensation. Urinary nerve growth factor levels could be a potential biomarker for the diagnosis of overactive bladder.